Evaluation of school diet and nutritional state among teenagers - Silva, Thiécla Katiane Rosales; Camargo, Gabriela Antunes; Coimbra Nuñez, Carla Evelyn; Cabreira Silva, Catiuscie; Reis Ballard, Cintia (Journal of Health Care, 2017)
Introduction and objective: The study aimed to evaluate the nutritional composition of the meals served in a state school in the Midwest region of Paraná, Brazil. Materials and methods: The evaluation was performed by analyzing the labels of the food used to prepare the meals, considering the quantification of total calories, total fat, saturated fat and trans fats, and comparing these values ??with the National School Feeding Programme (PNAE). Moreover, this study assessed the nutritional status of schoolchildren enrolled in the afternoon period by using anthropometric techniques, considering the following data: gender, age, weight, height, and body mass index. Results and discussion: In total, 154 adolescents of both genders were evaluated, with a mean age of 12.5 years (SDÂ±1.16). Among these, 66.88% were eutrophic and 31.17% were overweight (overweight and obesity). The average daily consumption per student relative to total calories, total fat, saturated fat and trans fats were: 355.30 kcal/day, 1.28%, 1.25%, and 0.22%, respectively. Only caloric intake was adequate with the reference values of legislation, representing 101.51% of adequacy. Conclusion: Overweight observed may have been favored by the existence of the school canteen and by poor eating habits. Thus, these data indicate both that school meals must be adequate and supply the nutritional needs in order to provide to students a good school performance as well as the importance of a professional nutritionist within schools, adjusting the composition of school lunches and contributing beneficially with actions to promote health, welfare and development of adolescents.